First record of Isegama Krombein (Hymenoptera, Chrysididae, Amiseginae) from China, with description of a new species - Li, Shuang-Shuang; Xu, Zai-Fu (Zootaxa, 2016)
The genus Isegama Krombein is recorded from China for the first time and one new species, Isegama sinica Li & Xu, sp. nov. (China: Guangxi, Hainan, Yunnan) is described and illustrated. Key to species of the genus is provided.